Revisiting Japan's External Adjustment Since 1985 - Meredith, Guy (IMF Working Papers; Working Paper ;, 1993)
The factors that explain Japan's external performance since the mid-1980s are controversial. While the current account surplus eventually declined following exchange rate changes in 1985-86, a widening since 1990 has led to renewed scepticism about the role of relative price movements in bringing about external adjustment. This paper revisits the post-1985 experience to determine whether it can be explained by traditional factors. The results indicate that, over the period as a whole, the behavior of trade volumes and prices was similar to that predicted by traditional relationships. In particular, relative price movements played an important role in reducing the surplus: in their absence, it would have widened further.